2004
DOI: 10.1159/000081761
|View full text |Cite
|
Sign up to set email alerts
|

Airway Wall Thickness in Patients with COPD and Healthy Current Smokers and Healthy Non-Smokers: Assessment with High Resolution Computed Tomographic Scanning

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is characterized by airflow obstruction caused by emphysema or airway narrowing, or both. Recently airway dimensions have been measured using high-resolution computed tomography (HRCT). To evaluate large and small airway dimensions by HRCT and compare them with pulmonary function tests in patients with COPD and in smokers with or without airflow obstruction. Methods: We used HRCT scanning to measure airway wall thickness at the segmental and sub-segmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 41 publications
4
41
1
Order By: Relevance
“…However, the presence of bronchial wall thickening or bronchiectasis seen at lobe-based visual assessment was associated with significant differences in the quantitative airway dimensions. Researchers in previous studies showed a significant but moderate degree of negative correlation between airway wall thickening and pulmonary function test results (5)(6)(7). Similarly, in the present study, the number of lobes with bronchial wall thickening at visual assessment showed moderate correlation with physiologic parameters.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, the presence of bronchial wall thickening or bronchiectasis seen at lobe-based visual assessment was associated with significant differences in the quantitative airway dimensions. Researchers in previous studies showed a significant but moderate degree of negative correlation between airway wall thickening and pulmonary function test results (5)(6)(7). Similarly, in the present study, the number of lobes with bronchial wall thickening at visual assessment showed moderate correlation with physiologic parameters.…”
Section: Discussionsupporting
confidence: 79%
“…The characteristic airflow limitation is progressive, not fully reversible, and associated with an abnormal inflammatory response of the lung to noxious particles or gases (1). With the development of volumetric computed tomography (CT), researchers in numerous studies have assessed the objective quantification of the extent and severity of pulmonary emphysema and measurements of airway dimensions (2)(3)(4)(5)(6)(7)(8)(9). There has also been increased interest in the use of CT to identify subphenotypes of COPD to facilitate physiologic management (treatment including watchful waiting), surgical strategy, selection for drug trials, and genetic analysis (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Substantial airway thickening in both diseases, as compared to healthy subjects, has been documented. [3][4][5]22 Airway wall thickening was observed in mild, moderate, and severe asthma, 4,5,18,22,23 but also in patients with cough-variant asthma. 24 Awadh et al found that patients with moderate and severe asthma had greater airway wall thickening than those with mild disease.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of high-resolution computed tomography (HRCT) offered new possibilities in the qualitative and quantitative assessment of airway (even as small as 1 mm in internal diameter) and lung tissue remodeling in asthma 1,2 and COPD. 1,3 There is evidence for the relationship between airway diameters measured in HRCT and results of other studies quantifying airway structure and function. [4][5][6][7] Moreover, HRCT seems a reliable tool in studying the changes in airway dimensions after nonspecific challenge tests, 8,9 the effect of bronchodilators, 6,10 and the consequences of airway remodeling (eg, air trapping).…”
Section: Introductionmentioning
confidence: 96%
“…They reported that moderate and severe COPD patients had greater airway wall thickening than healthy current smokers and healthy non-smokers as assessed by HRCT scanning; airway wall thickness is increased in healthy smokers who had normal spirometric values compared with normal controls. Wall thickness is inversely related to the degree of airflow obstruction, and positively related to cumulative smoking history 18) . Nakano et al reported a smaller airway lumen and an increased wall thickness in patients with COPD 19) .…”
Section: Discussionmentioning
confidence: 99%